2010
DOI: 10.4103/0250-474x.78529
|View full text |Cite
|
Sign up to set email alerts
|

Studies of antimicrobial activities of some 4-thiazolidinone fused pyrimidines, [1,5]-benzodiazepines and their oxygen substituted hydroxylamine derivatives

Abstract: Thiazolidin-4-one fused pyrimidines, [1,5]-benzodiazepines and their oxygen substituted hydroxylamine derivatives have been screened for antibacterial, antifungal and antimalarial activity. Bacillus subtilis, Escherichia coli, Proteus mirabilis and Salmonella typhi were used for antibacterial screening. Aspergillus fumigatus and Candida albicans were used for antifungal screening and Plasmodium species were used for antimalarial screening. The antibacterial and antifungal activities are expressed in terms of z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The needs for diverse inhibitors of α-Gls promote the search for novel classes of these molecules. As reported recently, pyrimidine-fused heterocyclic (PFH) compounds display various biological activities including anticancer activity, 11 antiviral activity, 12 antimicrobial activity, 13 antiinflammatory properties, antioxidant effects, and tyrosine kinase inhibitory activity.…”
Section: Research Articlementioning
confidence: 95%
See 1 more Smart Citation
“…The needs for diverse inhibitors of α-Gls promote the search for novel classes of these molecules. As reported recently, pyrimidine-fused heterocyclic (PFH) compounds display various biological activities including anticancer activity, 11 antiviral activity, 12 antimicrobial activity, 13 antiinflammatory properties, antioxidant effects, and tyrosine kinase inhibitory activity.…”
Section: Research Articlementioning
confidence: 95%
“…This strategy offers a powerful tool for preparing a new pyrimidine scaffold which has high potential for application in medicinal chemistry. The synthetic compounds were also characterized using different spectroscopic techniques such as 1 H-NMR, 13 C NMR, infrared (IR) and mass spectroscopies. The data clearly revealed that these molecules were produced successfully.…”
Section: Synthesis Of the Ligandsmentioning
confidence: 99%
“…This scaffold shows a broad spectrum of biological activities. The thienopyrimidines were assessed as antitumour [6][7][8][9], medicine [10], enzyme [11][12][13][14], phosphodiesterase inhibitors [15], antioxidative [16,17], antimalarial drug [18,19], antibacterial drug [20], antiviral [21], antifungal [22,23], medication [24], antiplatelet [25] and medicament [26]. In view of these observations, the varied biological property of thienopyrimidine pharmacophore impelled to synthesize the title compounds.…”
Section: Introductionmentioning
confidence: 99%
“…They show broad spectrum of biological activities due to their ready accessibility and diverse chemical reactivity [12,13]. They are involved in variety of applications such as antimicrobial, antibacterial, anticonvulsant, antifungal, anti-HIV, antiproliferative, anti-inflammatory, cystic fibrosis and antithyroid [14], etc.…”
Section: Introductionmentioning
confidence: 99%